EFFECT OF WORK EXPERIENCE, COMPETENCE, INDEPEDENCE, ACCOUNTABILITY, COMPLEXITY IN AUDIT QUALITY - Andreinald, Dahner; Rahmat Prayoga, Surya; Noviyanti Simorangkir, Enda (Journal of Research in Business, Economics, and Education, 2020)
Auditors are professions whose job is to audit financial statements. This study aims to obtain empirical evidence of the influence of Work Experience, Competence, Independence, Accountability, Complexity on Audit Quality. This research was conducted at a public accounting firm spread out in the city of Medan with the primary data collection method using questionnaire data. The number of samples analyzed there were 81 respondents using the sample determination method that is saturated sample. Data is valid and reliable, fulfilling the classic assumption test. The analysis technique used is Multiple Linear Regression with SPSS 25 software. The results of this study indicate that work experience, competence, independence, accountability, and complexity have a significant positive effect simultaneously and partially on audit quality